Genotypic shift of the hepatitis A virus and its clinical impact on acute hepatitis A in Korea: a nationwide multicenter study. (November 2013) - Kim, Ji Hoon; Yeon, Jong Eun; Baik, Soon Koo; Kim, Young Seok; Kim, Hong Soo; Park, Sang Hoon; Lee, Myung-Seok; Sohn, Joo Hyun; Lee, Jin-Woo; Choi, Sung Kyu; Kwon, So Young; Choi, Jong Young; et al.
Abstract Background: The genotypic shift of hepatitis A virus (HAV) and its correlation with clinical course has not been evaluated in acute hepatitis A (AHA). Methods: From June 2007 to May 2009, we prospectively enrolled 546 AHA patients. We performed a nested reverse transcriptase polymerase chain reaction (RT-PCR) using the serum samples in addition to phylogenetic analysis, then we compared patient clinical features. Results: Among 351 successfully genotyped patients, we found genotype IIIA in 178 patients (51%) and IA in 173 patients (49%). The sequences of genotype IA are identical to previously reported Korean genotype IA, and the new IIIA genotype is closely related to NOR24/Norway. We retrospectively analyzed 41 AHA samples collected from 2000 to 2006 and found that all of them were genotype IA. Patients with genotype IIIA showed significantly higher levels of aspartate aminotransferase, higher levels of alanine aminotransferase, and lower platelet counts than patients with genotype IA when comparing baseline laboratory data or peak/lowest laboratory data during the disease course. However, there were no differences in duration of hospital stay, incidence of cholestatic hepatitis, acute kidney injury, and acute liver failure, or mortality between them. Conclusions: A genotypic shift of the HAV was identified in Korean AHA subjects, and genotype IIIA HAV has become endemic. Although there were significant differences in the biochemical responses of AHA between genotype IA and genotype IIIA patients, we did not detect any differences in clinical outcomes such as complications or mortality.